Effect of dip-coating process on mechanical behavior of 3Y-TZP using different aging-free coatings. Issue 5 (1st March 2021) - Pereira, R.S.F.; Moura, C.G.; Henriques, B.; Chevalier, J.; Silva, F.S.; Fredel, M.C.
Abstract: 3Y-TZP discs were coated using 5Y-PSZ and 12Ce-TZP suspensions. Samples were evaluated in terms of roughness (Ra, Rq, Rz and Rsk), B3B flexural resistance, hardness, Young's modulus by instrumented indentation and surface damage resistance and Vickers hardness by impress Vickers measurements. Coatings with thickness of 7 μm were obtained. 3Y-TZP uncoated discs showed similar hardness and Young's modulus when compared to those coated with 5Y-PSZ. Discs coated with 12Ce-TZP had opposite behavior. Vickers and Berkovich hardness showed the same trend, with almost no difference observed between monolithic and the 5Y-PSZ coated samples, and with the 12Ce-TZP coated samples exhibiting lower hardness values. Coated samples presented lower flexural strength than uncoated ones. Correlation between roughness and B3B flexural strength was also performed, showing that surface quality achieved by the coating process is the one that rules the final resistance of the component, instead of the coating material.